Density, viscosity, excess properties, and spectral analyses of polyethylene glycol 300 and 1, 3-propane diamine binary system. (4th July 2022) - Qin, Xing; Li, Fu; Kong, Liting; Zhang, Rumeng; Liu, Xuan; Wu, Jialin; Zhang, Jianbin
ABSTRACT: This work reported the fundamental density ( ρ ) and viscosity ( η ) data of polyethylene glycol 300 (PEG) (1) + 1, 3-propane diamine (DAP) (2) binary system at T = (293.15 to 318.15) K and atmospheric pressure, in which excess-molar volume ( V m E ) of the binary system presented the lowest values when x1 was at 0.5. Concurrently, the η values increased firstly and diminished in the same composition range; when x1 was at 0.7, the η values of the binary system arrived at the largest values; and the smallest and largest viscosity deviation ( Δ η ) values of binary system were found at x1 ≈ 0.1 and x1 ≈ 0.6, respectively. Additionally, UV-Vis, FLS, 1 H-NMR and Raman spectral results suggested that there was hydrogen bonding of 'hydrogen atom in -OH groups of PEG binding nitrogen atom in -NH2 groups of DAP to form the hydrogen bonds of N···H-O'.